Towards a broader application of decision-making paradigms: a case study of the establishment of ECOWAS Cease-fire Monitoring Group (ECOMOG) - Domson-Lindsay, Albert (Rhodes University, Faculty of Humanities, Department of Political Studies, 2001)
The thesis in the main, looks at the decision-making process which underlined the Economic Community of West African States' attempt to end the Liberian crisis. It examines the establishment of ECOMOG to intervene in the Liberian civil crisis and the various pacific attempts to resolve the Liberian question. It does so through the medium of decision - making theory and some of the conceptual models that have flowed out of it. The thesis' focus on the decisional process of a regional body marks an attempt to broaden the scope of application of decision - making paradigms, which are usually employed to analyse decisions of national governments. The imperative for analysing the decisional process of ECOWAS in its quest to find solution to the Liberian problem has in part been dictated by the novelty of the ECOMOG concept. It marks the first major attempt of a sub - regional economic organization to successfully find solution to a civil conflict, as a result, there are numerous lessons to be gleaned from its failures and successes. Its relevance in the African context, with its intractable conflicts cannot be overemphasized. It has also been motivated by the fact that more works need to be produced on the decision-making processes of governments and regional bodies within the continent. The thesis argues that, both rational and "irrational" elements infused the decisional process of ECOW AS in its bid to solve the Liberian Crisis. Among other things, Policy-makers were influenced in their choice of decision by rational calculations based on national interest. It examines the clash of interests which characterized the establishment ofECOMOG as an tntervention force, the impasse this fostered and how it was eventually resolved. It postulates that exteljIlal actors influenced the decision process and that policy :Qiakers were aided to make the decisions they made by other organs in the decisional chain. The "irrational" component of the process, among other things, could be seen from the fact that the Liberian question was solved in " bits and pieces". Besides, blunders were committed through defective decision - making mechanism. The thesis concludes by offering suggestions to improve the quality of ECOW AS decision-making process with regard to conflict resolution and how to achieve regional consensus.
Keywords: Liberia -- History -- Civil War, 1989-1996|Liberia -- politics and government -- 1980-|Ecomog|Economic community of west african states